2014
DOI: 10.3109/00498254.2014.956848
|View full text |Cite
|
Sign up to set email alerts
|

Effects of capsaicin on pharmacokinetics of pitavastatin in rats

Abstract: 1. Capsaicin (CAP) is the primary pungent principle in peppers and an inhibitor of CYP3A subfamily and P-gp. 2. Pitavastatin is mainly metabolized via glucuronidation and metabolism by hepatic CYPs is minimal. Pitavastatin is taken up by Oatp1b2 (encoded by Slco1b2) in rat. 3. The pharmacokinetics results showed that AUC and Cmax in the group pre-treated with 3 mg/kg/d CAP were increased by 1.2 fold and 1.6 fold; AUC and Cmax in the group pre-treated with 8 mg/kg/d CAP were increased by 2.1 fold (p<0.05) and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…These findings provide in vivo evidence that NCH might have increased the bioavailability of fexofenadine via the inhibition of P-gp mediated drug efflux during the absorption phase in the intestine. Moreover, the results obtained in our study were comparable to previous reports where piperine [6], diosmin [23] substantially enhanced the bioavailability of fexofenadine through the inhibition of P-gp mediated efflux in intestine of rats. We have limited data regarding the pharmacokinetics and drug interactions of chrysin in humans; however, animal experiments showed that chrysin can influence the pharmacokinetics of different compounds (e.g., caffeine, nitrofurantoin, and paracetamol) due to its interactions with CYP enzymes and BCRP [24,7,25,26].…”
Section: Discussionsupporting
confidence: 90%
“…These findings provide in vivo evidence that NCH might have increased the bioavailability of fexofenadine via the inhibition of P-gp mediated drug efflux during the absorption phase in the intestine. Moreover, the results obtained in our study were comparable to previous reports where piperine [6], diosmin [23] substantially enhanced the bioavailability of fexofenadine through the inhibition of P-gp mediated efflux in intestine of rats. We have limited data regarding the pharmacokinetics and drug interactions of chrysin in humans; however, animal experiments showed that chrysin can influence the pharmacokinetics of different compounds (e.g., caffeine, nitrofurantoin, and paracetamol) due to its interactions with CYP enzymes and BCRP [24,7,25,26].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the modulatory effects of the phytochemicals on P-gp were evaluated in vivo by using doxorubicin as a model P-gp substrate. Although alteration in oral bioavailabilities of various drugs by combination with the pungent phytochemicals have been well demonstrated [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], no information is available regarding their effects on tissue distribution of P-gp substrates. Therefore, the tissue distribution of doxorubicin after intravenous injection were evaluated in mice pretreated with piperine, capsaicin, or [6]-gingerol.…”
Section: Discussionmentioning
confidence: 99%